Deported Americans : Life after Deportation to Mexico - Caldwell, Beth C., 1977- (Book collections on Project MUSE., 2019)
"Having interviewed over one hundred deportees and their families, Caldwell traces deportation's long-term consequences--such as depression, drug use, and homelessness--on both sides of the border. Showing how U.S. deportation law systematically fails to protect the rights of immigrants and their families, Caldwell challenges traditional notions of what it means to be an American and recommends legislative and judicial reforms to mitigate the injustices suffered by the millions of U.S. citizens affected by deportation."--Publisher's description